Don't tax me? Determinants of individual attitudes toward progressive taxation - Friedrich Heinemann; Tanja Hennighausen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This contribution empirically analyses the individual determinants of tax rate preferences. For that purpose we make use of the representative German General Social Survey (ALLBUS) that offers data on the individual attitudes toward progressive, proportional, and regressive taxation. Our theoretical considerations suggest that beyond self-interest, information, fairness considerations, economic beliefs and several other individual factors drive individual preferences for tax rate structures. Our empirical results indicate that the self-interest view does not offer the sole explanation for the heterogeneity in attitudes toward progressive taxation. Rather, we show that the choice of the favoured tax rate is also driven by fairness considerations.
Keywords: H89; D63; C42; A13; 330; tax progression; policy preferences; fairness; ALLBUS; Steuerprogression; Steuermoral; Meinung; Eigeninteresse; Gerechtigkeit; Deutschland